PENGEMBANGAN SISTEM INFORMASI PENYEWAAN LAPANGAN FUTSAL BERBASIS WEB (STUDI KASUS DI HAFIDZ FUTSAL SERANG-BANTEN) - Reni Haerani; Penny Hendriyati (JURSIMA, 2021)
Havidz futsal is one of the futsal field rental places on Jl. Raya Petir – Rangkas Serang – Banten. The futsal field rental system on the futsal havidz is currently still manual, the customer has difficulty knowing the futsal field schedule and requires customers to come to rent and arrange the desired rental schedule. To solve this problem, it is necessary to have a computerized system. With a computerized system, work will be easier, faster and more accurate than using a manual system. The purpose of this study is to create a futsal field rental information system that is more efficient in making the rental application process, providing the required information more easily and informatively for consumers and facilitating the management of rental report data for futsal fields owners. The research method used is a descriptive method, with the development of a system that uses the Classic Life Cycle method or commonly known as the waterfall method. This information system is built using the programming language PHP and MySQL as the database, the test method uses black box testing. This study produces an information system that can make it easier for customers who want to rent a futsal court without having to come to the futsal field first and customers can see the schedule directly by accessing the website. Keywords : Rental Information System, Futsal Field, MySQL, Waterfall